High temperature acclimation and termotolerance (TL50) in 6 varieties of Chenopodium quinua* - Sanabría A., Kimberlayn M. (2018)
The capacity of acclimatization at high temperature of 6 varieties (Kancolla, Salcedo, Ccoito, Negra collana, Pasancalla and Illpa) of Chenopodium quinoa Willd was studied. Quinoa plants were obtained from seeds, which grew in pots, in a grennhouse, until the phenological stage of 6 true leaves. These were exposed to a heat treatment in a growth chamber with a thermostat at 34/32 °C day/night (D/N) for 3 days and at low light intensity. The non-acclimated plants grew under the same conditions but at temperature of 22/20 °C D/N. The tolerance to high temperature was determined by exposing leaf discs at different times (8, 16, 32 and 64 min) at 50 °C (warm bath), measuring the thermostability of the cell membrane trough the loss of electrolytes with a conductimeter. The degree of thermotolerance was found according to the TL50 (time lethal to 50% of damage). The results showed that the varieties Pasancalla and Illpa presented acclimatization capacity, the most thermotolerant variety was the variety Illpa TL50 = 64 min when it was acclimatized and the most sensitive was Pasancalla TL50 = 8 min when it was not acclimatized. It was also observed that the percentage of cell damage increased as the exposure time to the high temperature was higher.